Lactate recovery kinetics in response to high-intensity exercises - Chatel, B.; Bret, C.; Edouard, P.; Oullion, R.; Freund, H.; Messonnier, L. A. (European Journal of Applied Physiology, 2016)
Purpose: The aim of this study was to investigate lactate recovery kinetics after high-intensity exercises. Methods: Six competitive middle-distance runners performed 500-, 1000-, and 1500-m trials at 90 % of their current maximal speed over 1500 m. Each event was followed by a passive recovery to obtain blood lactate recovery curves (BLRC). BLRC were fitted by the bi-exponential time function: La(t) = La(0) + A 1(1-e^-Gamma1t) + A 2(1-e^-Gamma1t), where La(0) is the blood lactate concentration at exercise completion, and Gamma1 and Gamma2 enlighten the lactate exchange ability between the previously active muscles and the blood and the overall lactate removal ability, respectively. Applications of the model provided parameters related to lactate release, removal and accumulation rates at exercise completion, and net amount of lactate released during recovery. Results: The increase of running distance was accompanied by (1) a continuous decrease in Gamma1 (p < 0.05), (2) a primary decrease (p < 0.05) and then a stabilization of Gamma2, and (3) a constant increase in blood concentrations (p < 0.05) and whole body accumulation of lactate (p < 0.05). Estimated net lactate release, removal and accumulation rates at exercise completion, as well as the net amount of lactate released during recovery were not significantly altered by distance. Conclusion: Alterations of lactate exchange and removal abilities have presumably been compensated by an increase in muscle-to-blood lactate gradient and blood lactate concentrations, respectively, so that estimated lactate release, removal and accumulation rates remained almost stable as distance increased.